Iron oxide synergistic vacuum carbothermal extraction of zinc from zinc sulfide - Ma H.-Z.; Dang Y.-B.; Wang Y.-N.; Zeng J.-Y.; Zhang X.; Guan M.-H.; Zhao X.-J. (Journal of Mining and Metallurgy. Section B: Metallurgy)
To reduce the issues of high pollutant emissions and lengthy processes in extracting zinc from zinc sulfide ore, a new technical approach involving the synergistic use of iron oxide and vacuum carbothermal reduction to extract zinc from zinc sulfide ore is proposed. The iron oxide is sourced from high-iron-content metallurgical residue. Under vacuum conditions, carbon reduces the iron oxide to metallic iron, which then displaces the zinc in the sulfide and produces zinc vapor. The zinc vapor is finally condensed to obtain metallic zinc. This study investigates the extraction of zinc from zinc sulfide under vacuum conditions using iron powder, pure iron oxide powder, and iron oxide from roasted cyanide tailings as iron sources. The main factors examined were the reduction temperature and the holding time on the zinc volatilization rate. The results show that at a molar ratio of nFe:nZn=1.1:1, a temperature of 1000 °C, and an initial furnace pressure of 10 Pa, iron powder, pure iron oxide powder, and iron oxide from roasted cyanide tailings can all achieve a zinc volatilization rate of over 99% from zinc sulfide. Different iron sources react with zinc sulfide to form FeS, and no sulfur-containing gases are produced in the zinc extraction process.